Socioeconomic disparities in psychological distress in a nationally representative sample of Japanese adolescents: A time trend study. (March 2017) - Kachi, Yuko; Abe, Aya; Ando, Emiko; Kawada, Tomoyuki
Objective: Socioeconomic status as a determinant of mental health problems has received scant attention in Japan, which has long been considered an egalitarian society. This study examined the association between socioeconomic status and psychological distress and its trends over 6 years among Japanese adolescents. Methods: We used data from a nationally representative sample of 9491 adolescents aged 12–18 years who participated in three repeated cross-sectional surveys between 2007 and 2013. The K6 scale was used to assess psychological distress. Socioeconomic status indicators included household income, parental education, parental working status and household structure. Results: Psychological distress prevalence decreased significantly from 2007 (10.7%) to 2013 (7.6%). However, the socioeconomic status patterns of psychological distress were consistent through the study period. Adolescents living in both lower (odds ratio = 1.61; 95% confidence interval = [1.27, 2.05]) and higher income households (odds ratio = 1.30; 95% confidence interval = [1.03, 1.62]) were more likely to report psychological distress than their middle-income counterparts. Adolescents with low household income were more likely to feel stress from interpersonal relationships and less likely to have help-seeking behaviors, while those with high household income were more likely to feel stress about school achievement. Psychological distress was also associated with parental poor education and single parenthood. Conclusions: Socioeconomic status disparities in adolescent psychological distress were evident and consistent during the 6-year period. There is a unique U-shaped relationship between household income and psychological distress among adolescents in Japan, unlike those from other countries. However, the underlying mechanisms may differ by income status. Future prevention efforts should consider socioeconomic status as a determinant of adolescent mental health problems.